Evaluasi Pengawasan oleh Bawaslu Sidoarjo: Penertiban Alat Peraga Kampanye dan Bahan Kampanye Pada Pilkada Kabupaten Sidoarjo 2024 - Imawan, Rifanda (Universitas Gajah Putih, 2026)
Election supervision is the responsibility of the Election Supervisory Board (Bawaslu) in accordance with Law Number 22 of 2007, including the supervision of Campaign Props (APK) and Campaign Materials (BK) to ensure compliance with the provisions of KPU Regulation Number 15 of 2023. However, the large number of violations related to the installation of APK and BK in Sidoarjo Regency, reaching 1,796 violation points, indicates weak compliance by election participants with regulations, as well as the limited authority of Bawaslu in taking direct enforcement actions. The purpose of this research is to evaluate the supervision carried out by the Sidoarjo Regency Election Supervisory Board in regulating Campaign Props (APK) and Campaign Materials (BK) during the 2024 Sidoarjo Regional Head Election (Pilkada), in accordance with the provisions of KPU Regulation Number 15 of 2023. This study uses a descriptive qualitative approach with the policy evaluation theory by Bridgman and Davis, which includes four indicators: input, process, outputs, and outcomes. The theory provides a comprehensive evaluation of Bawaslu Sidoarjo’s supervision of compliance with APK and BK regulations in the 2024 Pilkada, from policy design and implementation to its impact. Data were obtained through interviews with the Chairperson of Bawaslu Sidoarjo and documentation of campaign violations. The results show that although Bawaslu Sidoarjo has made various supervisory efforts, the success of enforcement is still hindered by its limited authority to impose direct sanctions. This study recommends the need to strengthen Bawaslu’s authority through regulatory revisions and the provision of direct sanctioning powers, enhance inter-agency synergy, and empower the role of the public and media in participatory supervision to reduce campaign violations in future elections.